2021
DOI: 10.1186/s12882-021-02308-y
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre prospective double blinded randomised controlled trial of intravenous iron (ferric Derisomaltose (FDI)) in Iron deficient but not anaemic patients with chronic kidney disease on functional status

Abstract: Background Iron deficiency (ID) is common in patients with chronic kidney disease (CKD). Intravenous (IV) iron in heart failure leads to improvement in exercise capacity and improvement in quality-of-life measurements; however, data in patients with CKD are lacking. Methods The Iron and the Heart Study was a prospective double blinded randomised study in non-anaemic CKD stages 3b-5 patients with ID which investigated whether 1000 mg of IV iron (fer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…One previous study has used two sample Mendelian randomisation to evaluate the relationship between iron biomarkers and sepsis, using a smaller cohort for identification of variants, and using a previously performed GWAS of sepsis in UK Biobank. 31 In common with our study, they identified associations with iron biomarkers and the odds of sepsis (OR for iron = 1.21, 95% CI = 1.13–1.29, p = 3.16 × 10 −4 ). However, this study included much fewer SNPs, as the GWAS used was around five to ten times smaller (n = 23,986 vs n = 246,139 for ferritin), meaning that only two SNPs were included for iron status, and three SNPS included for transferrin saturation and ferritin.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One previous study has used two sample Mendelian randomisation to evaluate the relationship between iron biomarkers and sepsis, using a smaller cohort for identification of variants, and using a previously performed GWAS of sepsis in UK Biobank. 31 In common with our study, they identified associations with iron biomarkers and the odds of sepsis (OR for iron = 1.21, 95% CI = 1.13–1.29, p = 3.16 × 10 −4 ). However, this study included much fewer SNPs, as the GWAS used was around five to ten times smaller (n = 23,986 vs n = 246,139 for ferritin), meaning that only two SNPs were included for iron status, and three SNPS included for transferrin saturation and ferritin.…”
Section: Discussionsupporting
confidence: 88%
“…The odds ratio for sepsis with each increasing standard deviation of TSAT from our meta-analysis of both cohorts (1.11, 95% CI 1.05-1.20), should be put in the context that taking an oral iron supplement transiently increases TSAT by around 2-3 standard deviations for around 8 hours 35 ; while intravenous iron increases TSAT by around a standard deviation for at least three months in non-anaemic populations with chronic kidney disease. 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4 trial metaanalysis also suggested treatment with intravenous ferric carboxymaltose was associated with a reduction in recurrent cardiovascular hospitalisations in systolic heart failure patients [21]. Also, in iron deficient non anaemic chronic kidney disease patients a recent randomised controlled trial suggested a trend to an improved quality of life and reduction in brain naturetic peptide (BNP) [22]. Anaemia significantly increases the risk of morbidity and mortality in CKD [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recently published study in non-dialysis kidney patients who were non-anaemic but iron deficient did not report any statistical significant beneficial effect of iron therapy on exercise capacity at 4 or 12 weeks, but did show numerical improvements in exercise capacity measurement in the iron therapy group [ 13 ]. This trial had a small sample size and there were imbalances in baseline exercise capacity between groups, which may account for the non-significant outcome.…”
Section: Introductionmentioning
confidence: 99%